Catchment characteristics and water chemistry of over 5000 nationally monitored Swedish lakes - Lackner, Anna; Back, Emil (Swedish University of Agricultural Sciences, 2026)
This dataset contains data for catchment characteristics and lake water chemistry for lakes in the Swedish Lake Survey, SLS (omdrevstationer), and trend lake (trendlakestationer) monitoring programs. Both surveys, the Swedish Lake Survey and the trend lake survey, are compiled at the Swedish University of Agricultural Sciences (SLU) as part of the university's environmental monitoring and assessment programme Lakes and Watercourses. This makes up a dataset of 5140 lakes (110 of which are trend lakes monitored 4 times a year and 5030 survey lakes monitored every 6 years, some lakes are in both programs), all >1 ha in lake area. For each of these programs this dataset includes (1) time series of water chemistry for all the stations, (2) shapefile with the catchment delineation and station coordinates, and (3) a file summarizing catchment characteristics. Catchment characteristics include land cover, soil depth, peat coverage, ditch density, ditch density in peat areas, NDVI, lake water chemistry, atmospheric deposition, precipitation, temperature, precipitation as snow, percentage above the high coast line, and runoff.

This dataset also includes the code used to extract the data used to generate this time series and characteristics. As such this data can be reproduced, and extended from the information contained in the dataset.

The following files are included in the dataset:

**Documentation**
readme_overview.md: An overview of what the dataset contains (further elaborated in readme_data.md) and how it was generated (further elaborated in readme_code.md).

readme_data.md: Documentation of the final datasets files, including units, reference to the code used to generate, and original data source.

readme_code.md: Documentation of the code and functions used to generate the dataset. A static version can be found in the dataset as git_freeze and a live version of the code can be found at https://github.com/aalackner/DOC_catchments.

**Data**
chemistry_SLS.csv: 14107 x 46, 4.8MB
chemistry_trend.csv: 16018 x 46, 5.1MB

characteristics_SLS.csv: 5030 x 81, 6MB
characteristics_trend.csv: 110 x 93, 0.16MB

SLS.zip: 6194 polygons, 20MB
trend.zip: 111 polygons, 0.3MB

etc.zip: 114 MB
etc.zip is a folder with additional timeseries data used in the calculation of characteristics.

Detta dataset innehåller data för avrinningskarakteristika och vattenkemiska data för sjöar i övervakningsprogrammen Sveriges sjömätning, SLS (omdrevstationer) och trendlakestationer (trendlakestationer). Data till Sveriges sjömätning (SLS) och trendlakestationer (trend) samlas in vid Sveriges lantbruksuniversitet (SLU) som en del av universitetets miljöanalysprogram Sjöar och vattendrag. Detta utgör ett dataset med 5140 sjöar (varav 110 är trendsjöar som övervakas fyra gånger om året och 5030 undersökningssjöar som övervakas vart sjätte år, flera sjöar är båda trendstationer och omdervstationer), alla >1 ha i sjöyta. För vart och ett av dessa program innehåller datasetet (1) tidsserier av vattenkemi för alla stationer, (2) en shapefil med avrinningsområdets avgränsning och stationskoordinater, och (3) en fil som sammanfattar avrinningsområdets egenskaper. Avrinningsområdets egenskaper inkluderar marktäckning, jorddjup, torvtäckning, dikestäthet, dikestäthet i torvområden, NDVI, sjöns vattenkemi, atmosfärisk deposition, nederbörd, temperatur, nederbörd som snö, procentandel över den höga kustlinjen och avrinning.

Datasetet innehåller även den kod som används för att extrahera de data som används för att generera tidsserien och dess egenskaper.

Följande filer ingår i datasetet:

**Dokumentation**
readme_overview.md: En översikt över vad datasetet innehåller (mer detaljerat i readme_data.md) och hur det genererades (mer detaljerat i readme_code.md).

readme_data.md: Dokumentation av de slutliga datasetfilerna, inklusive enheter, hänvisning till den kod som använts för att generera dem och den ursprungliga datakällan.

readme_code.md: Dokumentation av den kod och de funktioner som använts för att generera datasetet. En statisk version finns i datasetet som git_freeze och en liveversion av koden finns på https://github.com/aalackner/DOC_catchments.

**Data**
chemistry_SLS.csv: 14107 x 46, 4,8 MB
chemistry_trend.csv: 16018 x 46, 5,1 MB

characteristics_SLS.csv: 5030 x 81, 6 MB
characteristics_trend.csv: 110 x 93, 0,16 MB

SLS.zip: 6194 polygoner, 20 MB
trend.zip: 111 polygoner, 0,3 MB

etc.zip: 114 MB
etc.zip är en mapp med ytterligare tidsseriedata som används vid beräkningen av egenskaper.
Avrinningsområdets egenskaper och vattenkemi i över 5000 nationellt övervakade svenska sjöar
Keywords: WATER QUALITY/WATER CHEMISTRY; WATERSHED CHARACTERISTICS; water monitoring; vattenövervakning; catchment; upptagningsområde; water chemistry; catchment scale; long term monitoring; water quality monitoring; Hydrography; Hydrografi; land cover; lakes; Environmental monitoring and assessment; Miljöanalys; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Elevation; Höjddata; Environment; Miljö; Inland Waters; Sjöar och vattendrag